Secure hybrid power-frequency multiple access in satellite terrestrial communication systems: a performance study - Huu Q. Tran; Viet-Thanh Pham (Universitas Ahmad Dahlan, 2026)
This paper investigates a secure hybrid power–frequency multiple access (PFMA) framework for satellite–terrestrial communications. By integrating power- and frequency-domain multiplexing, PFMA achieves approximately 4 dB lower transmit signal-to-noise ratio (SNR) than non-orthogonal multiple access (NOMA) for the same connection outage probability (COP) at SNR > 0 dB, and it reduces the COP by up to 30% at low-to-medium SNRs. It further decreases the intercept probability (IP) by 20–25% at PS = 10 dBm. Closed-form COP and IP expressions are derived under shadowed-Rician fad ing with both internal and external eavesdroppers and validated via Monte Carlo simulations. Parameter analysis indicates that PFMA’s SNR gain can either ex tend coverage by 60% or save 37% energy, providing design guidelines for 6G, satellite IoT, and emergency communication systems. The single-cell assump tion points to future work on multi-cell and mobility scenarios.